Reputation in travel and tourism: a perspective article. Issue 1 (18th November 2019) - Inversini, Alessandro
Abstract : Purpose: This paper aims to discuss the evolution of the concept of reputation towards online reputation and real time reputation assessment and management. It starts by outline the role of reputation within the branding literature and explains the advantages of having a good (online) reputation. The final section looks into the future of reputation assessment and analysis introducing the concept of real time reputation assessment and management. Design/methodology/approach: To compile this study, secondary research was conducted; relevant literature was presented in a narrative way to outline core concepts about past and future perspectives on reputation. Findings: State-of-the-art literature indicates the importance of reputation and the shift towards online reputation. Building on this, the aggregation of social media along with the growing computational power is actually giving the possibility of real-time reputation assessment grasping reputation breakdowns in an instantaneous way. Originality/value: Literature presents a series of review about the topic of reputation from different angles. This contribution aims at bridging the gap between reputation and online reputation opening the floor for possible discussions about the future of real-time reputation management.